Assessing protein immunogenicity with a dendritic cell line-derived endolysosomal degradome. - Matthias Egger; Alexander Jürets; Michael Wallner; Peter Briza; Silke Ruzek; Stefan Hainzl; Ulrike Pichler; Claudia Kitzmüller; Barbara Bohle; Christian G Huber; Fátima Ferreira (PLoS ONE, 2011)
The growing number of novel candidate molecules for the treatment of allergic diseases imposed a dramatic increase in the demand for animal experiments to select immunogenic vaccines, a pre-requisite for efficacy. Because no in vitro methods to predict the immunogenicity of a protein are currently available, we developed an in vitro assay that exploits the link between a protein's immunogenicity and its susceptibility to endolysosomal proteolysis.We compared protein composition and proteolytic activity of endolysosomal fractions isolated from murine bone marrow- and human blood- derived dendritic cells, and from the dendritic cell line JAWS II. Three groups of structurally related antigen variants differing in their ability to elicit immune responses in vivo (Bet v 1.0101 and Bet v 1.0401, RNases A and S, holo- and apo-HRP) were subjected to in vitro simulated endolysosomal degradation. Kinetics and patterns of generated proteolytic peptides were evaluated by gel electrophoresis and mass spectrometry.Antigens displaying weak capacity of T cell priming in vivo were highly susceptible to endolysosomal proteases in vitro. As proteolytic composition, activity, and specificity of endolysosomal fractions derived from human and murine dendritic cells were comparable, the JAWS II cell line could be used as a substitute for freshly isolated human or murine cells in in vitro degradation assays.Endolysosomal fractions prepared from the JAWS II cell line provide a reliable tool for in vitro estimation of protein immunogenicity. The rapid and simple assay described here is very useful to study the immunogenic properties of a protein, and can help to replace, reduce, and refine animal experiments in allergy research and vaccine development in general.